IPO underpricing phenomenon on the karachi stock exchange - Sohail Khalid, Muhammad; Raheman, Abdul; Zakaria, Muhammad; Farhat, Rehana (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
In this study the risk-adjusted performance of IPO firms listed on the KSE from 2000 to 2012 is analyzed. The objective is to provide insights of the underpricing (first trading day) of IPOs and to find out the determinants of underpricing in the light of asymmetric information and signaling theories. The results indicate that underpricing prevails on the KSE. The level of underpricing with regard to the marked adjusted model is found to be 28.28 percent for the full sample of 83 IPOs, which shows that investors can make a market adjusted profit of 28.28 percent by investing in new issues of IPO firms. The profit opportunity for the day traders is also observed. The year-wise analysis of the level of underpricing shows that the overall amount of level of underpricing decreased over the succeeding years. Furthermore, the level of underpricing is observed in all sectors except equity investment instruments, technology hardware and equipment and personal goods. The risk adjusted performance of IPO firms is also measured with the help of five models by using matched firm techniques. The level of underpricing is observed to be 39.64 percent for the market adjusted model, 42.63 percent for market model, 42.31 percent for CAPM, 42.84 percent for the Fama-French three-factor model and 42.99 percent for the four-factor model. The results indicate that the choice of model does not matter while measuring the risk adjusted returns of IPO firms on the first trading day.
Argumenta Oeconomica, 2018, Nr 2 (41), s. 225-255
Keywords: tracking error; matched firms; underpricing; IPOs; KSE